Force calculation using analytical and CAE methods for thin-blade slotting process - Yazdan Kordestany; Yongsheng Ma (Cogent Engineering, 2017)
A multi-spindle slotting process is taken as the case to analyse the mechanism involved in the cutting process affecting the machining efficiency. The analysis techniques used in this research include force analysis through existing analytical and numerical models and implementing the results to conduct an in-depth analysis of the cutting dynamics. The input parameters considered are blade geometry, cutting speed, and feed rate to investigate their effects on tool life. The study of dynamics of the cutting process was also extended to determine the effect of chatter vibration by determining the stability lobe diagram of the process. Results coupled from these two primary parts of the investigation were used to identify optimal processing conditions. The approaches employed to specify conditions for the stability lobe diagram showed that the method can be applied to analyse different combinations of tool and workpiece materials. Finite element methods along with the obtained force are then applied to simulate the static force distribution for a circular saw blade. The determined blade deformation and a CAD/CAE software are used for the optimization process. Finally, it is possible to compare the resulting deformations for both optimized and original blade geometries.